Study of Inhibition of Apha6 Gene in Acinetobacter Baumanii by Satureja and Thyme Essence with Rt-Pcr Technique - Saghi, Hossein; Bahador, Abbas; Esmaeili, Davoud (The International Journal of Biotechnology, 2014)
Increasing isolation of multidrug-resistant Acinetobacter baumannii (MDR) has been reported in worldwide and it is recently one of the most difficult nosocomial acquired gram-negative pathogens to control and treatment.These bacteria are one of ESBL producing that great potential have for the rapid development of antibiotic resistance. The indecorous use of antibiotics is often associated with adverse effects on the human health.Because of Satureja and Thyme essence has antimicrobial properties so they can be used against infections caused by MDR Acinetobacter baumannii. With attention to increase in population and tendency to lesser use of synthetic drugs, many of these of medicinal herbs have been replaced. The present study was aimed to investigate the inhibitory effects of Satureja khuzestaniea and Thyme essence against the expression of antibiotic resistance genes aphA-6 and compare to Housekeeping DNA gyraseA in strains of Acinetobacter baumannii with RT-PCR Technique. The major components of Satureja khuzestaniea essence were carvacrol (90.88%), ρ-cymene (3.11%), ϒ terpinene (1.24%), linalool (0.91%) and Thyme essence were thymol (28.8%) and carvacrol (23.46%). Satureja khuzestaniea with MIC (0.3 μl / ml) and Thyme with MIC (0.45μl / ml) has the effect of reducing the expression of antibiotic resistance genes aphA-6 but these are essence no inhibitory effect on the housekeeping DNA Gyrase-A gene. This study indicated that these are essence have inhibitory effects against gene expression of antibiotic resistance aphA-6 with high MIC. Because these are essence has a good inhibitory effect against MDR Acinetobacter baumanii and, aphA-6 gene expression so it can be used as therapeutic complementary no side effects against this bacterium.